A review of the Botany, phytochemistry, pharmacology and toxicology of Arctotis arctotoides (L.f.) O.Hoffm. (Asteraceae) - Grierson, D.; Otang, W.M.; Afolayan, A.J. (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Arctotis arctotoides (Asteraceae) is used by the rural people of the Eastern Cape for the treatment of epilepsy, indigestion and catarrh of the stomach, and the leaf juice or paste is applied topically to treat wounds and skin disorders. Unfortunately, no previous reviews are available for this important medicinal plant. Hence, the aim of this review is to provide a comprehensive overview of the botany, phytochemistry, pharmacology and toxicology of Arctotis arctotoides. Methodology: This review was carried out using a comprehensive and systematic literature search on the following databases: Google Scholar, PubMed, Science Direct and Scopus. Searches were undertaken using the key word “Arctotis arctotoides” and the six synonyms of Arctotis arctotoides identified in the Plant List. Results: In the first phytochemical study of Arctotis arctotoides, the authors reported that sesquiterpenoids predominated in the root oil while the essential oils of the leaves, flowers and stems had both monoterpenoids and sesquiterpenoids. The literature survey reveals that Arctotis arctotoides has been investigated in four pharmacological areas, including antibacterial, antifungal, anticancer and anti-oxidant activities. Three toxicity screens for the crude extracts of A. arctotoides on cell lines, rats and brine shrimp were identified in the literature. Conclusion: Studies detailing the bioactivity of the crude extracts and the isolated phytochemicals have provided partial evidence regarding the traditional use of A. arctotoides in the treatment of wounds in the Eastern Cape of South Africa. However, in order to fully exploit the medicinal potential of A. arctotoides, the expansion of existing traditional knowledge into the bordering communities where the plant is not currently used for the stated indications will support the greater use of the plant in primary healthcare.